A new approach for steady state analysis of three-phase SEIG feeding single-phase load. Issue 1 (27th November 2018) - Benhacine, Tarek Zine Eddine; Nesba, Ali; Mekhtoub, Said; Ibtiouen, Rachid
Abstract : Purpose: This paper aims to deal with a modified-based approach for the evaluation of the steady state performances of three-phase self-excited induction generator (SEIG) feeding single-phase load. Design/methodology/approach: Using the symmetrical components method, the proposed approach is based on a modified model of unbalanced three-phase SEIG, which is formulated similarly to the well-known model of balanced three-phase SEIG. Owing to this modified model, the determination of the SEIG operating point amounts to the resolution of two semi-decoupled nonlinear equations for two unknowns; the magnetizing reactance and the per-unit frequency. A simple resolution method based on an iterative two-step technique is used. The results obtained by the proposed approach are compared with those given by a conventional approach and are validated experimentally. Findings: The proposed approach is as accurate as the conventional approach. Further, for the same accuracy degree, the proposed approach permits to speed up the resolution when compared to the conventional approach, as only few iterations are required for the convergence. The proposed approach was also successfully used for the steady state analysis of SEIG under generalized unbalanced loading conditions. Practical implications: The determination of the operating point of the generator is based on a modified model of the generator and a simple iterative resolution method. The calculation technique can be implemented on low resource controller to provide online voltage control of the SEIG. Originality/value: The paper contains two main originalities. The first one consists in a modified formulation of the SEIG model under unbalanced loading conditions. The modified formulation permits the use of the well-known model of balanced three-phase SEIG. Unlike previous ones reported in the literature, the proposed model does not require tedious algebraic manipulations. The second originality is the use of two-step technique to solve the equations, which permits to avoid laborious mathematical derivations and manipulating high-order polynomials.